Short-term Low Glycemic Diet Improves Diet Quality But Not Feelings of Hunger or Salivary Ghrelin Levels in Preschoolers: A Pilot Study. (7th June 2021) - Hasan, Faten; Weltman, Arthur; Patrie, James; Gaylinn, Bruce; Kranz, Sibylle
Abstract: Objectives: Internal and external factors, including glycemic index (GI), regulate food intake in adults, but little is known about the effect of GI on appetite in children. We examined how low- GI (high fiber) diet changed energy intake, diet quality (Healthy Eating Index 2015 (HEI-2015)), self-reported feelings of hunger, and salivary ghrelin in preschoolers. Methods: In this prospective, randomly controlled clinical trial of 22 healthy preschoolers (age 48 ± 7.2 mo, 31.8% females, 73% normal weight) participated in 4 "day camps" of 2 low-GI (INT) and 2 high-GI (CON) days at the Laboratory. Intake, HEI-2015 scores, and pre- and post-lunch hunger ratings were measured. In a subsample of n  = 7, salivary ghrelin (pre-prandial, 60- and 120- min post-prandial) were measured. Ordinal GEE regression models and proportional (prop) odds ratios were used to compare appetite ratings; geometric means were used to compare intakes, diet quality, and ghrelin levels. Results: On the INT diet, children had more fiber ( P  < 0.001) and lower GI and GL ( P  < 0.01), but energy, carbohydrate, fat, and protein intakes were similar. Mean HEI-2015 scores were 85.2 and 59.4 on INT and CON, respectively ( P  < 0.01). Hunger ratings and salivary ghrelin levels were not different between the diets; hunger ratings were not correlated with ghrelin levels. Assessment time was the only significant predictor of appetite at 60-min (OR = 2.04 95% CI: 1.30, 3.19, P  = 0.002) and 120-min (OR = 1.92, 95% CI: 1.09, 3.38, P  = 0.022). Children who reported feeling "hungry" pre-prandial were more likely to report "full" at 60-min on INT (Prob 0.48, 95% CI: 0.29, 0.68) versus CON (Prob 0.47, 95% CI: 0.29, 0.66). The opposite trend was observed at 120-min, as those who had reported "hungry" were more likely to report "full" on CON (Prob 0.42, 95% CI: 0.25, 0.62) versus INT (Probability 0.24, 95% CI: 0.11, 0.45). Conclusions: The intervention showed significant better diet quality and lower GI/GL on the INT diet, but no differences in hunger or salivary ghrelin levels. Surprisingly, salivary ghrelin was not correlated with hunger ratings, suggesting a need to better understand the role of ghrelin on appetite regulation in children. Funding Sources: This study was funded by the University of Virginia Curry Initiative Fund.